Regulation der glomerulären Schlitzmembran - Worthmann, K.; Schiffer, Mario (Nieren- und Hochdruckkrankheiten, 2012)
The integrity of the glomerular filter with its barrier function is important for homoeostasis of plasma proteins. The podocytes build the outer layer of the filtration barrier and the glomerular capillaries are completely surrounded by foot processes of podocytes. The space between these foot processes, the filtration slits, are covered by a specialized protein structure the "slit diaphragm". This protein structure consists of complexes of transmembrane proteins with an interacting extracellular part and an intracellular part which functions as an important signaling hub. This signaling hot spot has been shown to influence many important signaling pathways within the podocyte. Over the past years there is a large body of evidence that podocytes and the structures that are built by podocytes are not static but are mobile and that there is a constant adaptation of the foot processes. This is only achieved by a tight orchestration of the signaling mechanisms that regulate surface expression of slit-diaphragm proteins. In this review we focus on signaling pathways that regulate the turnover and the surface expression of the slit diaphragm protein nephrin. The different isoforms of the protein kinase C family seem to play an important role in this process. The better understanding of these processes regulating nephrin surface expression could lead to novel therapeutical strategies for the treatment of proteinuria. © 2012 Dustri-Verlag Dr. Karl Feistle.
CRIS-Team Scopus Importer:2020-11-12
Keywords: Cofilin-1; Nephrin; PKCα; PKCε; PKCλ/ι; Podocyte